Watchman LAA Closure Device in Patients with AF - Rizzo, Toni (MD Conference Express, 2014)
This article presents the results from the Watchman Left Atrial Appendage System for Embolic Protection in Patients With Atrial Fibrillation trial [PROTECT AF; NCT00129545] that compared the Watchman left atrial appendage device with warfarin therapy for patients with atrial fibrillation.